Method for forming a three-dimensional electrode structure

JP7917110B2Active Publication Date: 2026-09-08LG ENERGY SOLUTION LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2025500868
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-07-12
Filing Date
2023-07-11
Publication Date
2026-09-08
Estimated Expiration
2043-07-11

AI Technical Summary

Benefits of technology

【0033】 本出願は、解析用3次元電極構造体を形成する方法、前記方法が保存されたハードウェア装置および前記解析用3次元電極構造体の形成システムを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007917110000001
    Figure 0007917110000001
  • Figure 0007917110000002
    Figure 0007917110000002
  • Figure 0007917110000003
    Figure 0007917110000003
Patent Text Reader

Abstract

The present application can provide a method for forming a three-dimensional electrode structure for analysis, a hardware device storing the method, and a formation system for the three-dimensional electrode structure for analysis. In the present application, a method capable of effectively forming an electrode structure having excellent conformity to an actual electrode can be provided. Further, in the present application, a method capable of forming an electrode structure in which the type and volume characteristics of an actual electrode are appropriately reflected can be provided. In the present application, a method capable of simply, rapidly, and efficiently forming the electrode structure as described above can be provided.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This application claims priority rights based on Republic of Korea Patent Application No. 10-2022-0085868 dated July 12, 2022, and all content disclosed in the documents of the said Korean patent application is incorporated herein by reference.

[0002] This application relates to a method for forming a three-dimensional electrode structure, a hardware device in which the method is stored, and a system for forming the three-dimensional electrode structure for analysis. [Background technology]

[0003] Digital twin technology is a technique that creates a virtual replica of a real-world object in a computer and predicts the outcome by simulating situations that could occur in reality.

[0004] Such digital twin technology can be applied in a variety of fields.

[0005] For example, digital twin technology can be used in the research and development of secondary batteries.

[0006] A rechargeable battery is a device that stores electrical energy in the form of chemical energy and then generates electricity when needed, and it can be charged and discharged. With the expansion of the electric vehicle market, there is a demand for the development of rechargeable batteries that are highly stable and can achieve high energy density, and digital twin technology can be applied in the development of such rechargeable batteries.

[0007] For example, Patent Document 1 discloses a method for modeling a three-dimensional electrode structure through digital twin technology.

[0008] The method disclosed in Patent Document 1 combines so-called 3D structure formation technology and 3D structure reconstruction technology to form an electrode structure.

[0009] However, the above method forms the electrode structure using the same method regardless of the type of electrode, resulting in poor matching to the actual electrode, inability to form a structure that reflects the volume characteristics of the electrode, and a lack of systematic verification techniques for the formed electrode structure. [Prior art documents] [Patent Documents]

[0010] [Patent Document 1] Republic of Korea Patent Publication No. 10-2021-0063821 [Overview of the project] [Problems that the invention aims to solve]

[0011] This application provides a method for forming a three-dimensional electrode structure for analysis, a hardware device in which the method is stored, and a system for forming the three-dimensional electrode structure for analysis.

[0012] This application provides a method for effectively forming electrode structures that exhibit excellent matching to actual electrodes.

[0013] Furthermore, this application provides a method for forming an electrode structure that appropriately reflects the actual type and volume characteristics of the electrode.

[0014] This application provides a method for forming the aforementioned electrode structure simply, quickly, and efficiently. [Means for solving the problem]

[0015] This application relates to a method for forming a three-dimensional electrode structure.

[0016] The method may include the steps of: setting the volume of the sample structure; forming an initial electrode structure having the formed sample structure volume; and verifying the initial electrode structure.

[0017] The method may further comprise the step of providing design parameters of an electrode sample to set the volume of the sample structure.

[0018] In the above, the design parameters may be one or more selected from the group consisting of type of electrode material, content of electrode material, shape of electrode material, mechanical physical properties of electrode material, electrode loading level, electrode density, and dispersion rate of the material in the electrode thickness direction.

[0019] The step of setting the volume of the sample structure may comprise: (1) forming a sample electrode structure by using the design parameters; and (2) setting the volume of the sample structure through downsizing the sample electrode structure.

[0020] In the above, step (2) may comprise the step of checking structural parameters of each electrode structure with reduced volume while reducing the volume of the sample electrode structure.

[0021] In the above, the structural parameters may be one or more selected from the group consisting of volume fraction of conductive material, tortuosity and specific surface area.

[0022] The minimum volume at which the error rate of the structural parameters of the electrode structure with reduced volume in step (2) relative to the structural parameters of the sample electrode structure is 10% or less may be designated as the volume of the sample structure.

[0023] In the above, the volume reduction of the electrode structure may be performed such that the resulting volume is 0.1 to 0.5 times the volume of the electrode structure before volume reduction.

[0024] When forming the sample electrode structure, the electrode materials may be formed in descending order of their volume fraction within the electrode.

[0025] In the above, when forming the initial electrode structure, the electrode materials may be formed in descending order of their volume fraction within the electrode.

[0026] During the verification of the initial electrode structure, a step can be performed in which the structural parameters of the initial electrode structure are compared with the structural parameters of the electrode sample.

[0027] The aforementioned structural parameters may be one or more selected from the group consisting of the effective electrical conductivity of the conductive material, the degree of void flexibility, and the interface area between the active material and the void.

[0028] In the above, if the absolute value of the error rate between the structural parameters is 5% or more, the step of correcting the electrode structure can be further performed.

[0029] In the above, if the error rate with respect to the effective electrical conductivity of the conductive material, which is a structural parameter, is 5% or more, the contact angle between the active material and the conductive material or between the active material and the binder in the electrode material can be corrected in the direction of 90 degrees, and if the error rate is -5% or less, the contact angle can be corrected in the direction away from 90 degrees.

[0030] In the above, if the error rate with respect to the structural parameter of the degree of curvature of the void is 5% or more, a correction can be performed in the direction of decreasing the contact angle between the active material and the conductive material or between the active material and the binder in the electrode material, and if the error rate is -5% or less, a correction can be performed in the direction of increasing the contact angle.

[0031] In the above, if the error rate for the structural parameter, the interface area between the active material and the air gap, is 5% or more, the contact angle between the active material and the conductive material or between the active material and the binder in the electrode material can be reduced, and if the error rate is -5% or less, the contact angle can be increased.

[0032] This application also relates to a hardware device on which the method described above is stored. [Effects of the Invention]

[0033] This application provides a method for forming a three-dimensional electrode structure for analysis, a hardware device in which the method is stored, and a system for forming the three-dimensional electrode structure for analysis.

[0034] This application provides a method for effectively forming electrode structures that exhibit excellent matching to actual electrodes. Furthermore, this application provides a method for forming electrode structures that appropriately reflect the type and volume characteristics of actual electrodes.

[0035] This application provides a method for forming the aforementioned electrode structure simply, quickly, and efficiently. [Brief explanation of the drawing]

[0036] [Figure 1] This is a flowchart showing the process by which the method of this application is carried out. [Figure 2] This is a schematic diagram illustrating the process of obtaining the volume of a sample structure. [Figure 3] This is a diagram showing the sequence for forming the electrode structure. [Figure 4] This is a diagram illustrating the process for determining effective electrical conductivity. [Figure 5] This is a schematic diagram illustrating the process of correcting the electrode structure through the contact angle. [Modes for carrying out the invention]

[0037] This application relates to a method for forming a three-dimensional electrode structure, and more specifically, to a method for forming a three-dimensional electrode structure for analysis using digital twin technology.

[0038] The aforementioned three-dimensional electrode structure for analysis is a twin of an actual electrode (electrode sample) realized through digital twin technology, and can represent an electrode structure that can be applied to various simulations.

[0039] Figure 1 is a flowchart showing a method for forming an electrode structure according to an example of this application.

[0040] As shown in Figure 1, the method of this application may include at least the steps of: setting the representative elementary volume (REV) (S100); forming the electrode structure (S200); and verifying the electrode structure (S300).

[0041] The aforementioned term, Sample Structure Volume (REV), refers to the minimum volume of an electrode structure that can provide measurement results representative of an actual electrode.

[0042] The aforementioned sample structure volume may also refer to the volume of an electrode structure that can be calculated to the same value as the actual electrode with minimal calculations.

[0043] In this application, by first setting the volume of the sample structure and then forming the electrode structure according to the set result, and then going through a verification stage, it is possible to form an electrode structure that has a high degree of matching to the actual electrode and effectively reflects the volume characteristics of the actual electrode.

[0044] The volume of the sample structure can be set based on design parameters.

[0045] The aforementioned design parameters are information relating to the electrode applied to form the electrode structure, and refer to information relating to the actual electrode (hereinafter referred to as the electrode sample).

[0046] Therefore, the method of this application may further include, as a step prior to the step of setting the volume of the sample structure, a step of providing the design parameters or a step of obtaining the design parameters.

[0047] The design parameters may include one or more selected from the group consisting of the type of electrode material, the content of the electrode material, the shape of the electrode material, the mechanical properties of the electrode material, the electrode loading level, the electrode density, and the dispersion rate of the material in the electrode thickness direction.

[0048] The information regarding the type of electrode material may include, for example, information regarding the type of electrode active material such as positive electrode active material and negative electrode active material, the type of conductive material, the type of binder, the type of electrolyte, the type of current collector and / or the type of separation membrane, as materials for forming the electrode.

[0049] The information regarding the content of the electrode material may include information regarding the content of the electrode active material, conductive material, binder and / or electrolyte within the electrode, as well as the ratio of their respective contents.

[0050] The information relating to the shape of the electrode material may include, for example, information relating to the shape of the particles and particle size distribution when the materials constituting the electrode active material, conductive material, binder and / or electrolyte are in particle form.

[0051] The information relating to the mechanical properties of the electrode material may include information relating to true density or deformation rate; the information relating to the electrode loading level may include information relating to the amount of electrode active material (negative electrode active material or positive electrode active material) per unit area of ​​the electrode; and the information relating to the dispersion rate of the electrode material in the electrode thickness direction may include information relating to the distribution of the electrode material (active material, binder, conductive material and / or electrolyte, etc.) in the electrode thickness direction.

[0052] There are no particular restrictions on the method of obtaining or providing the aforementioned design parameters. Such parameters can be obtained through methods using 3D formation technology, 3D reconstruction technology, or a combination of both.

[0053] For example, the design parameters may be provided through a method in which the user inputs relevant information considering design values, a method in which the relevant information is retrieved from a database built for electrode samples, and / or an image analysis method. The image analysis method is a method of obtaining design parameters through image analysis of electrode samples, and such methods are well known. For example, the method can analyze images obtained by a high-resolution nanoscale 3D X-ray microscope, a FIB-SEM (Focused Ion Beam-Scanning Electron Microscope), and / or an EDX (Energy Dispersed X-ray Spectroscopy).

[0054] The information necessary to form an initial structure using digital twin technology and the methods for obtaining that information are publicly known, and in this application, a sample electrode structure for setting the volume of the sample structure can be formed through such a publicly known method.

[0055] The step of setting the sample structure volume may include (1) forming a sample electrode structure using at least one of the design parameters and (2) setting the sample structure volume through downsizing of the sample electrode structure.

[0056] In step (1) above, the sample electrode structure can be formed by inputting the design parameters into an interface for realizing a digital twin and realizing the electrode structure in three dimensions.

[0057] Software and hardware capable of realizing the electrode structure are known in the field of digital twin technology, and in this application, the electrode structure can be realized using such known software and / or hardware.

[0058] In step (1) above, the sample electrode structure is formed to have an arbitrarily set predetermined initial volume.

[0059] In step (2) above, a process is carried out to obtain the volume of the sample structure by downsizing the sample electrode structure that was formed to have the initial volume.

[0060] Step (2) may include a step of reducing the volume of the sample electrode structures while confirming the structural parameters of each electrode structure whose volume has been reduced.

[0061] The aforementioned step involves iteratively extracting smaller electrode structures from a sample electrode structure, calculating and comparing structural parameter values ​​for the extracted electrode structures, and obtaining a volume (sample structure volume) that can produce the same result values ​​as the actual electrode with minimal calculation.

[0062] Examples of the aforementioned structural parameters include, but are not limited to, the volume ratio of conductive material within the electrode, the degree of flexibility, and the specific surface area.

[0063] In step (2) above, the step of reducing the volume of the sample electrode structure and confirming the structural parameters of each electrode structure whose volume has been reduced may be carried out until the structural parameters show an error rate of 5% or more compared to the initial value.

[0064] In the above, the initial value of the structural parameter is the value of the structural parameter relative to the sample electrode structure. That is, the structural parameter of the electrode structure maintains a substantially constant level as the volume of the electrode structure decreases, but when the volume of the electrode structure becomes smaller than the volume of the sample structure, it begins to show an error of a certain level or more relative to the initial value. Therefore, the minimum volume at which the error of the structural parameter relative to the initial value is within a certain level can be specified as the volume of the sample structure.

[0065] Specifically, the sample structure volume may be specified as the minimum volume in which the structural parameters exhibit an error rate of 10% or less compared to the initial value. In one example, the sample structure volume may be specified as the minimum volume in which the structural parameters exhibit an error rate of 9% or less, 8% or less, 7% or less, 6% or less, or 5% or less compared to the initial value. There are no special restrictions on the lower limit of the error rate to which the minimum volume specification applies, and in one example, the error rate may be approximately 0% or more, 1% or more, 2% or more, 3% or more, 4% or more, or 5% or more. In one example, the sample structure volume may be the minimum volume in which at least one of the structural parameters, the volume ratio of the conductive material, the degree of curvature, and the specific surface area, exhibits an error rate within the range compared to the initial value, or the minimum volume of an electrode structure in which all of the structural parameters, the volume ratio of the conductive material, the degree of curvature, and the specific surface area, exhibit an error rate within the range.

[0066] In the above, the error rate is the absolute value of △P, calculated by the following equation 1.

[0067] [Formula 1] ΔP = 100 × (Pf - Pi) / Pi

[0068] In Equation 1, Pi is the initial value of the structural parameter (e.g., the initial value of the volume ratio, curvature, or specific surface area of ​​the conductive material), and Pf is the structural parameter of the electrode structure with reduced volume (e.g., the volume ratio, curvature, or specific surface area of ​​the electrode structure with reduced volume).

[0069] There are no special restrictions on the volume (initial volume) of the sample electrode structure set in the aforementioned process; an appropriate volume can be specified taking into account the volume of the electrode sample.

[0070] For example, the volume of the sample electrode structure may be approximately 400 μm in both width and length, while having an arbitrary thickness. The thickness of the structure may be specified to an appropriate value considering the size of the electrode actually applied and the efficiency of the method of this application.

[0071] Furthermore, there are no special restrictions on the method of reducing the volume (initial volume) of the sample electrode structure set in the above process; the volume can be reduced in stages at a constant ratio to the initial volume. For example, the volume reduction can be carried out such that the volume of the electrode structure after reduction becomes approximately 0.1 to 0.5 times the volume of the electrode structure before reduction. The ratio of the volume may be approximately 0.15 times or more, 0.2 times or more, or 0.25 times or more, or 0.45 times or less, 0.4 times or less, 0.35 times or less, 0.3 times or less, or 0.25 times or less.

[0072] The above process can be explained as follows with reference to the example in Figure 2.

[0073] The leftmost electrode structure in Figure 2 is a sample electrode structure realized using digital twin technology, and is an electrode structure having an arbitrarily set initial volume (in the case of Figure 2, a volume of 400 μm × 400 μm × electrode thickness μm).

[0074] To realize the aforementioned sample electrode structure, electrode materials are illustrated three-dimensionally in a virtual space according to the design parameter information. In this application, in this process, electrode materials can be illustrated three-dimensionally in a virtual space in order of the largest volume they occupy within the electrode. Depending on the type of electrode, there are differences in the types of materials that form the electrode, and there are also differences in the ratio of the volume occupied by each electrode material in each electrode. Conventionally, electrode structures were realized by illustrating electrode materials in an arbitrary order without considering such differences, but in this application, electrode materials can be illustrated in order of the largest volume they occupy within the electrode.

[0075] According to this method, the order in which the electrode structure is realized will change depending on the type of electrode. For example, when the electrode to be realized is for a lithium-ion battery / lithium-sulfur battery, the electrode structure is formed by first forming the electrode active material, followed by the conductive material and binder, as shown in Figure 3 (CASE 1). When it is an electrode for an all-solid-state battery, the electrode structure is formed in the order of electrode active material, solid electrolyte, and conductive material / binder (CASE 2). When it is an electrode for a lithium-air battery, the electrode structure is formed in the order of void layer, catalyst particles, and conductive material / binder (CASE 3).

[0076] By forming the electrode structure in a manner in which the electrode materials are arranged in descending order of their volume ratio within the electrode, the ratio of the error between the measured value and the actual electrode can be minimized.

[0077] In downsizing, as shown in Figure 2, structures of a specific size smaller than the sample electrode structure are repeatedly extracted. In Figure 2, structures are extracted while repeatedly reducing the horizontal and vertical lengths (400 μm) of the sample electrode structure by 1 / 4 each time.

[0078] Structural parameter values ​​are calculated for each electrode structure iteratively extracted through the above process in order to determine the volume of the sample structure.

[0079] The aforementioned structural parameters are parameters related to the performance of the battery that can be derived from the electrode structure, and examples of these include the volume ratio of conductive material, degree of flexibility, and / or specific surface area, as mentioned above.

[0080] Methods for calculating the structural parameters in electrode structures are well known. For example, the volume fraction (ε) and tortuosity (τ) of the conductive material can be calculated using a method for calculating the effective electrical conductivity (σeff) of the electrode structure. The effective electrical conductivity is the charge conduction characteristic that can actually be exhibited by the electrode, calculated considering the volume fraction (ε) and tortuosity (τ) of the conductive material, and is expressed by equation σ eff =(ε / τ 2 Since it is calculated as ) × σ (in the above formula σ eff σ is the effective electrical conductivity, ε is the volume fraction of the conductive material, τ is the degree of flexibility, and σ is the intrinsic conductivity of the conductive material. The volume fraction and degree of flexibility can be confirmed through the calculation of the effective electrical conductivity.

[0081] The effective electrical conductivity can be calculated, for example, by applying the continuity equation of Ohm's law as the governing equation, as illustrated in Figure 4, and by applying the Dirichlet boundary condition under the assumption that a constant voltage difference of 1V is maintained between opposing surfaces on the coaxial cable.

[0082] The aforementioned volume ratio and degree of curvature can also be calculated using a method that quantifies the number and shape of voxels, which are the smallest units constituting the structure.

[0083] Furthermore, the specific surface area, as a structural parameter, is a value obtained by dividing the surface area of ​​the electrode material per unit volume or the interface area between different materials by the volume of the electrode. Such parameters can also be calculated using a method that quantifies the number and / or shape of the voxels.

[0084] In publicly known software capable of realizing digital twin technology, there are algorithms that can verify the parameters through the quantification of the number and shape of voxels, as described above, and in this application, the parameters can be verified through such an algorithm.

[0085] As described above, the sample structure volume can be determined by repeatedly checking the structural parameters, up to the point just before the error rate of the relevant structural parameter relative to its initial value begins to exceed a certain level. The graph shown in the lower right of Figure 2 is the result of determining the sample structure volume through this process, and in the example in Figure 2, the sample structure volume is approximately 6.25 × 10⁻⁶. 4 μm 3 It is specified to a certain extent.

[0086] In the method of this application, after determining the volume of the sample structure by the above method, the step of forming an electrode structure having the corresponding volume of the sample structure (hereinafter referred to as the initial electrode structure) is carried out.

[0087] The method for carrying out the step of forming the initial electrode structure can be substantially the same as the method for forming the sample electrode structure in step (1), except that the electrode structure is formed to have the volume of the sample structure.

[0088] Based on the provided design parameters, an electrode structure having the sample structure volume can be formed and used as the initial electrode structure.

[0089] In this process, as in the formation of the sample electrode structure, the electrode structure can be formed by three-dimensionally illustrating the electrode materials in a virtual space in order of the largest volume they occupy within the electrode, thereby ensuring the advantages described above. Therefore, for example, when the electrode to be realized is an electrode for a lithium-ion battery / lithium-sulfur battery, the electrode structure can be formed by first forming the electrode active material, followed by the conductive material and binder, as shown in Figure 3; when it is an electrode for an all-solid-state battery, the electrode structure can be formed in the order of electrode active material, solid electrolyte, and conductive material / binder; and when it is an electrode for a lithium-air battery, the electrode structure can be formed in the order of void layer, catalyst particles, and conductive material / binder.

[0090] The method of this application allows for the verification of the initial electrode structure after it has been formed.

[0091] Such a step may include comparing the structural parameters of the initial electrode structure with the structural parameters of an electrode sample (actual electrode).

[0092] The structural parameters to be confirmed in the above process may be one, two, or all three of the following: the effective electrical conductivity of the conductive material, the degree of curvature of the void, and the interface area between the active material and the void.

[0093] In the above, the degree of curvature of the void is a concept included in the degree of curvature among the structural parameters confirmed for electrode structures that are repeatedly extracted in order to determine the volume of the sample structure, and the interface area between the active material and the void is a concept included in the specific surface area among the structural parameters confirmed for electrode structures that are repeatedly extracted in order to determine the volume of the sample structure.

[0094] The degree of curvature of the void and the interface area between the active material and the void can be determined by known methods, and can be determined in accordance with the method for determining the degree of curvature and specific surface area, which are structural parameters confirmed for electrode structures that are repeatedly extracted in order to determine the volume of the sample structure.

[0095] For example, as exemplarily shown in FIG. 4, the effective electrical conductivity can be calculated by a method in which the continuity equation of Ohm's law is applied as a governing equation, and a Dirichlet boundary condition is applied under the assumption that a voltage difference of 1 V on coaxially opposing surfaces is maintained constant.

[0096] Methods for obtaining said structural parameters for an initial electrode structure embodied by digital twin technology and an actual electrode sample are known, and such known methods can be applied in the present application.

[0097] When the error rate between the structural parameter of said initial electrode structure and the structural parameter of the electrode sample (actual electrode) is below a certain level, said initial structure can be designated as a final electrode structure.

[0098] In the above, the error rate is ΔV calculated by the following Equation 2.

[0099] [Formula 2] ΔV=100×(V R -V I ) / V R

[0100] In Equation 2, V I is the structural parameter of said initial electrode structure (for example, said effective electrical conductivity, void tortuosity, or interfacial area between active material and void), and V R is the structural parameter of said electrode sample (actual electrode) (for example, said effective electrical conductivity, void tortuosity, or interfacial area between active material and void).

[0101] The above process can be carried out until the error rate falls, for example, within a range of approximately -5% to 5%, or within a range of -3% to 3%.

[0102] In other words, an initial electrode structure can be designated as the final electrode structure if the error rate between the structural parameters of the initial electrode structure and the structural parameters of the electrode sample (actual electrode) is within the range of -3% to 3% or -5% to 5%.

[0103] For example, an initial structure may be designated as a final structure if at least one of the structural parameters, effective electrical conductivity, air gap curvature, and the interface area between the active material and the air gap, exhibits an error rate within the aforementioned range. In other examples, an initial electrode structure may be designated as a final electrode structure if all of the structural parameters, effective electrical conductivity, air gap curvature, and the interface area between the active material and the air gap, exhibit an error rate within the aforementioned range.

[0104] If at least one, two or more, or all of the aforementioned structural parameters—effective electrical conductivity, void curvature, and the interface area between the active material and the void—exceed the aforementioned ranges in terms of error rate, the electrode structure correction step may be carried out.

[0105] Such a correction step for electrode structures can be carried out by correcting the connection shape between materials within the electrode structure and the shape of the conductive material and binder. For example, as shown in Figure 5, the correction can be carried out by modifying the shape of the conductive material and binder so that the contact angle between the active material and the conductive material / binder is controlled.

[0106] The method for performing the correction for each structural parameter is not particularly limited.

[0107] For example, in the case of the effective electrical conductivity of the conductive material, if the error rate confirmed by the above method is 3% or more or 5% or more, the contact angle between the active material and the conductive material or the contact angle between the active material and the binder in the electrode material can be corrected in the direction of 90 degrees, and if the error rate is -3% or less or -5% or less, the contact angle can be corrected in the direction away from 90 degrees.

[0108] In the above, correcting the contact angle in the 90-degree direction means performing a correction so that the contact angle approaches 90 degrees. Therefore, if the contact angle is less than 90 degrees, a correction is performed to increase the contact angle, and if it exceeds 90 degrees, a correction is performed to decrease the contact angle. At this time, there is no particular limit to the degree to which the angle is corrected; for example, the correction can be performed so that the contact angle increases or decreases by 5 degrees at a time. Methods for performing such corrections using digital twin technology are publicly known.

[0109] In the above, correcting the contact angle away from 90 degrees means performing a correction so that the contact angle moves away from 90 degrees. Therefore, if the contact angle is less than 90 degrees, a correction is performed so that the contact angle becomes smaller, and if it exceeds 90 degrees, a correction is performed so that the contact angle becomes larger. At this time, there is no particular limit to the degree to which the angle is corrected, and for example, the correction can be performed so that the contact angle becomes larger or smaller by 5 degrees. A method of performing such a correction using digital twin technology is publicly known.

[0110] On the other hand, if the error rate with respect to the air gap curvature, which is a structural parameter, is 3% or more or 5% or more, the contact angle between the active material and the conductive material or between the active material and the binder in the electrode material will be reduced, and if the error rate is -3% or less or -5% or less, the contact angle will be increased. In this process, there are no particular restrictions on the degree to which the angle is corrected, and for example, the correction can be performed so that the contact angle increases or decreases by 5 degrees. Methods for performing such corrections using digital twin technology are well known.

[0111] Furthermore, if the error rate for the structural parameter, the interface area between the active material and the air gap, is 3% or more or 5% or more during the above process, the contact angle between the active material and the conductive material or between the active material and the binder in the electrode material can be reduced. If the error rate is -3% or less or -5% or less, the correction can be performed in a direction that increases the contact angle. In this process as well, there are no particular limitations on the degree to which the angle is corrected; for example, the correction can be performed so that the contact angle increases or decreases by 5 degrees at a time. Methods for performing such corrections using digital twin technology are well known.

[0112] After going through the correction process described above, the structure verification process is carried out again, and if the error rate falls within the aforementioned certain level, the structure in question can be set as the target final structure.

[0113] This application also relates to a hardware device on which a method for forming the electrode structure is stored.

[0114] Furthermore, this application relates to an electrode structure formation system in which the aforementioned hardware device is used.

[0115] The system may further include a device for collecting the design parameters applied in the method for forming the electrode structure. There are no particular limitations on the type of such device, and examples include a specimen preparation device for cutting an electrode sample to produce multiple specimens and / or an imaging device for taking images of the electrode sample and / or specimens.

Claims

1. A method for forming a three-dimensional electrode structure through digital twin technology, The step of setting the volume of the sample structure, The steps include forming an initial electrode structure having the set sample structure volume, The step of verifying the initial electrode structure and forming the three-dimensional electrode structure. Includes, The step of setting the volume of the sample structure is, (1) The step of forming an electrode structure with an initial volume using design parameters, (2) The step of setting the sample structure volume by downsizing the electrode structure having the initial volume. Includes, The aforementioned design parameters are design parameters for the actual electrode sample, and consist of one or more selected from the group consisting of the type of electrode material, the content of the electrode material, the shape of the electrode material, the mechanical properties of the electrode material, the electrode loading level, the electrode density, and the dispersion rate of the material in the electrode thickness direction. In the stage of verifying the initial electrode structure, a step is performed to compare the structural parameters of the initial electrode structure with the structural parameters of the actual electrode sample. The method wherein the structural parameter is one or more selected from the group consisting of the effective electrical conductivity of the conductive material, the degree of curvature of the void, and the interface area between the active material and the void.

2. The method according to claim 1, wherein step (2) includes a step of checking the structural parameters of each electrode structure whose volume has been reduced while reducing the volume of the electrode structure having the initial volume.

3. The method according to claim 2, wherein the structural parameter of step (2) is one or more selected from the group consisting of the volume ratio of the electrically conductive material, the degree of inflexibility, and the specific surface area.

4. The method according to claim 2, wherein, in step (2) above, the minimum volume at which the error rate of the structural parameters of the electrode structure whose volume has decreased with respect to the initial values ​​is 10% or less is designated as the sample structure volume, and the initial values ​​are the structural parameters of the electrode structure having the initial volume.

5. The method according to claim 2, wherein the reduction in the volume of the electrode structure having the initial volume is carried out so that the volume becomes 0.1 to 0.5 times the volume of the electrode structure having the initial volume before the volume reduction.

6. The method according to claim 1, wherein the electrode materials are formed in order of decreasing volume ratio within the electrode when forming the electrode structure having the initial volume.

7. The method according to claim 1, wherein the electrode materials are formed in order of decreasing volume ratio within the electrode when the initial electrode structure is formed.

8. The method according to claim 1, further comprising the step of correcting the electrode structure when the absolute value of the error rate between the structural parameters of the initial electrode structure and the structural parameters of the actual electrode sample is 5% or more.

9. If the error rate of the structural parameter, the effective electrical conductivity of the conductive material, is 5% or more, the contact angle between the active material and the conductive material or between the active material and the binder in the electrode material is corrected in the 90-degree direction. The method according to claim 8, wherein if the error rate is -5% or less, the contact angle is corrected in a direction away from 90 degrees.

10. If the error rate with respect to the aforementioned structural parameter, the degree of curvature of the gap, is 5% or more, the contact angle between the active material and the conductive material or between the active material and the binder in the electrode material is reduced. The method according to claim 8, wherein the contact angle is increased when the error rate is -5% or less.

11. If the error rate of the structural parameter, which is the interface area between the active material and the air gap, is 5% or more, the contact angle is reduced. The method according to claim 9, wherein the contact angle is increased when the error rate is -5% or less.

12. A hardware device that stores a program for causing a processor to perform the method according to any one of claims 1 to 11.

13. A program for causing a processor to perform the method described in any one of claims 1 to 11.

Citation Information

Patent Citations

  • Method for predicting energy density of negative electrode material of lithium ion battery based on neural network

    CN109376933A

  • Lithium ion battery performance prediction model and construction method and application thereof

    CN111062137A

  • Method, device and equipment for predicting lithium deposition of three-electrode lithium ion battery and medium

    CN113420475A

  • Lithium ion battery simulation method and device, electronic equipment and readable storage medium

    CN114117737A

  • Electrode simulation method and device for all-solid battery, and method of manufacturing electrode for all-solid battery

    JP2017059444A